Antidepressant-like Effects of Young Areca Nut n-Hexane Extract Using Forced Swim Test in Mice Tested Individually - Novianty, Riryn; Yuharmen, Yuharmen; Sofiyanti, Nery; Ya’la, Fitra Audhi (Jurnal Media Informatika, 2024)
Depression is a common neuropsychiatric disorder that occurs in humans regardless of gender and age. Areca catechu, as a local plant, can be utilized as an antidepressant to treat depression. The current investigation aimed to determine the antidepressant action from an n-hexane extract of young areca nut using the Forced Swim Test (FST) as a standard method in screening antidepressants validated by the behavior of animals. Short-term medication or acute FST was performed by injecting mice with extract at doses 10 and 50 mg/kg, while the mice were treated with the best dose in long-term medication or sub-chronic FST. A day after the re-test on sub-chronic FST, toxicity test was performed. The extract at the dose of 50 mg/kg possessed antidepressant action during acute and sub-chronic FST. The results of the phytochemical analysis stated that the saponins and steroids present in the young areca nut n-hexane extract may be the active constituents that act as antidepressants. No toxic effects were detected from the young areca nut n-hexane extract in mice that had been injected for 7 consecutive days. n-Hexane extract from young areca nut presents antidepressant potential.